Nonapeptides Arginine Vasotocin and Isotocin in Fishes: Advantage of Bioactive Molecules Measurement - Sokołowska, Ewa; Gozdowska, Magdalena; Kulczykowska, Ewa (Frontiers in Marine Science, 2020)
The aim of this article is to share with fish physiologists and behaviourists our thoughts and hints regarding the involvement of nonapeptides in various physiological and behavioural processes in fishes and the advantage of measurements of bioavailable molecules. Arginine vasotocin (AVT) and isotocin (IT) are biologically active nonapeptides in teleosts which are produced in separate neurosecretory neurons in the hypothalamic nuclei. They act as neurotransmitters and/or neuromodulators in the central nervous system (CNS) or as peripheral hormones, when they are released in the neurohypophysis and distributed via the bloodstream. Biosynthesis of bioactive AVT and IT is a complicated multistage process and nonapeptides have multiple sites of action. Different analytical approaches, including determination of pro-AVT and pro-IT mRNA in the hypothalamus or AVT and IT concentration in the brain, pituitary and plasma are used depending on the aim of the study. However, the level of biologically-active molecules is more straightforwardly related to their current action in the CNS and/or peripheral organs compared with indirect proxies of nonapeptides production such as the expression of pro-peptides mRNA. Therefore analysis of AVT and IT is highly recommended in many studies. Herein we compiled various works in which bioavailable AVT and IT were analysed in order to highlight the importance of such approach. Moreover, we compared the fluctuation of nonapeptide levels in the plasma with that in the brain of round gobies in successive reproductive phases. We also showed that neither AVT nor IT level was associated with fish age.